Application of Ionic Liquids based Microwave-Assisted Extraction to Bioactive Compounds Comfrey (Symphytum officinale L.) Leaves - Hasan, Nahrul; Mun'im, Abdul; Hayun, Hayun (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Extraction of bioactive compounds from comfrey leaves (Symphytum officinale L.) was carried out by comparing organic solvents and ionic liquids between conventional and microwave-assisted extraction (IL-MAE) methods. The comfrey leaf powder was extracted under various conditions. The types of organic solvents used are 65% ethanol and ionic liquids. The extraction methods used are reflux and microwave-assisted extraction. The ionic liquid was extracted by microwave-assisted extraction with the following conditions: ionic liquid concentration of 1 mol/L, the solid-liquid ratio of 1:20 (g/mL), extraction time of 10 minutes, and power of 30% (270 Watt). The total phenolic content of the extract was analyzed with a microplate reader. Allantoin and retrorsine N-oxide levels were analyzed by thin-layer chromatography – densitometry. MAE extraction in a solvent containing 65% ethanol resulted in the highest total phenolic content of 1.038±0.012. The highest levels of allantoin were also obtained from MAE extraction with 65% ethanol solvent at 2.922 ± 0.123. The highest levels of retrorsine N-oxide were obtained by extraction of MAE with (BMIM)Br with a concentration of 0.049 ± 0.007. Extraction of comfrey leaves using the MAE method of 65% ethanol produced the highest total phenolic and allantoin content compared to other methods. (BMIM) Br extraction with MAE can attract the highest retrorsine N-oxide in comfrey leaves.  Abstrak: Ekstraksi senyawa bioaktif daun komfrey (Symphytum officinale L.) dilakukan dengan membandingkan pelarut organik dan cairan ionik, antara metode konvensional dengan metode microwave assisted extraction. Serbuk daun komfrey diekstraksi dengan berbagai kondisi. Jenis pelarut organik yang digunakan yaitu etanol 65% dan cairan ionik. Metode ekstraksi konvensional yang dilakukan, yaitu refluks dan microwave-assisted extraction. Cairan ionik diekstraksi denganmicrowave-assistedextraction dengan kondisi: konsentrasi Cairan ionik 1 mol/L, Rasio padatcair 1:20 (g/mL), waktu ekstraksi 10 menit dan power 30% (270 Watt). Kadar fenol total dalam ekstrak dianalisis dengan microplate reader. Sedangkan kadar allantoin dan retrorsine N-oxide dianalis dengan kromatografi lapis tipis–densitometri. Ekstraksi MAE dengan pelarut etanol 65% menghasilkan kadar fenol total tertinggi, yaitu 1,038 ± 0,012. Kadar Allantoin tertinggi didapatkan juga dari ekstraksi MAE dengan pelarut etanol 65% sebanyak 2,922 ± 0,123. Kadar retrorsin N-oksida tertinggi didapatkan dengan ekstraksi MAE dengan (BMIM) Br dengan konsentrasi 0,049 ± 0,007. Ekstraksi daun komfrey dengan metode MAE etanol 65% menghasilkan kadar fenol total dan allantoin paling tinggi dibandingkan dengan metode lain. Ekstraksi (BMIM) Br dengan MAE dapat menarik kadar retrorsin N-oksida paling tinggi dalam daun komfrey.